In vivo manipulation of stem cells for adipose tissue repair/reconstruction. (November 2011) - Yoshimura, Kotaro; Eto, Hitomi; Kato, Harunosuke; Doi, Kentaro; Aoi, Noriyuki
Many features of adipose stem/progenitor cells, including their physiological functions and localization, have been clarified in the past decade. Adipose tissue turns over very slowly, with perivascular progenitor cells differentiating into new adipocytes to replace dead adipocytes. A number of clinical trials using freshly isolated or cultured adipose-derived stromal cells containing adipose progenitor/stem cells are ongoing. Therapeutic use of adipose stem/progenitor cells has been shown to promote angiogenesis and adipose tissue regeneration. Identification of adipocyte-releasing factors upon apoptosis/necrosis would be a breakthrough and could lead to the next stage for adipose tissue regeneration. Activation of precursors in perichondrium and periosteum shows a dramatic neogenesis by simple injection and is an ideal example of in situ tissue engineering. The 'hit and catch'' strategy using a mobilizer of bone-marrow stem/progenitor cells (hit) and attractants to lead the cells to proper homing into the target tissue (catch) may be the future of stem cell manipulation. Careful design of the microenvironment, cell delivery protocol to avoid unexpected behavior and induce maximal potential, and selection of target diseases, will be critical to the success of clinical applications of adipose-derived stromal cells.